Visual Function in Mice with Photoreceptor Degeneration and Transgenic Expression of Channelrhodopsin 2 in Ganglion Cells - Thyagarajan, Senthil (J Neurosci, 2010)
The progression of rod and cone degeneration in retinally degenerate (rd) mice ultimately results in a complete loss of photoreceptors and blindness. The inner retinal neurons survive and several recent studies using genetically targeted, light activated channels have made these neurons intrinsically light sensitive. We crossbred a transgenic mouse line expressing channelrhodopsin2 (ChR2) under the control of the Thy1 promoter with the Pde6b(rd1) mouse, a model for retinal degeneration (rd1/rd1). Approximately 30–40% of the ganglion cells of the offspring expressed ChR2. Extracellular recordings from ChR2-expressing ganglion cells in degenerated retinas revealed their intrinsic light sensitivity which was ∼7 log U less sensitive than the scotopic threshold and ∼2 log U less sensitive than photopic responses of normal mice. All ChR2-expressing ganglion cells were excited at light ON. The visual performance of rd1/rd1 mice and ChR2 rd1/rd1 mice was compared. Behavioral tests showed that both mouse strains had a pupil light reflex and they were able to discriminate light fields from dark fields in the visual water task. Cortical activity maps were recorded with optical imaging. The ChR2rd1/rd1 mice did not show a better visual performance than rd1/rd1 mice. In both strains the residual vision was correlated with the density of cones surviving in the peripheral retina. The expression of ChR2 under the control of the Thy1 promoter in retinal ganglion cells does not rescue vision.